2022
DOI: 10.3390/ncrna8040055
|View full text |Cite
|
Sign up to set email alerts
|

miR-218: A Stress-Responsive Epigenetic Modifier

Abstract: Understanding the epigenetic role of microRNAs (miRNAs) has been a critical development in the field of neuropsychiatry and in understanding their underlying pathophysiology. Abnormalities in miRNA expression are often seen as key to the pathogenesis of many stress-associated mental disorders, including major depressive disorder (MDD). Recent advances in omics biology have further contributed to this understanding and expanded the role of miRNAs in networking a diverse array of molecular pathways, which are es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Strikingly, mir-135b showed the highest fold increase (2.51) in fish exposed to low pH. When upregulated, this miRNA helps protect against neuroinflammation and oxidative stress (Schell et al, 2022); the latter stressors have been correlated with hair cell degradation and hearing loss in zebrafish, mice, and humans (Huang et al, 2000;Canlon et al, 2013;Chen et al, 2022). (Lewis et al, 2016, Lewis et al, 2009 Mature miRNA sequences listed with bold nucleotides are non-conserved regions; dashes represent gaps within in the annotated sequence when aligned to the model organism.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, mir-135b showed the highest fold increase (2.51) in fish exposed to low pH. When upregulated, this miRNA helps protect against neuroinflammation and oxidative stress (Schell et al, 2022); the latter stressors have been correlated with hair cell degradation and hearing loss in zebrafish, mice, and humans (Huang et al, 2000;Canlon et al, 2013;Chen et al, 2022). (Lewis et al, 2016, Lewis et al, 2009 Mature miRNA sequences listed with bold nucleotides are non-conserved regions; dashes represent gaps within in the annotated sequence when aligned to the model organism.…”
Section: Discussionmentioning
confidence: 99%
“…Transient inhibition of miRNA-218 in the dorsal hippocampus in early postnatal life resulted in the disruption of early depolarizing GABAergic signaling, structural defects in dendritic spines in CA1, and increased intrinsic membrane excitability in CA3 pyramidal neurons resulting in a heightened hippocampal network activity and a predisposition to seizures. Previous work has shown that miRNA-218 is implicated in embryonic motor neuron development (Amin et al, 2015(Amin et al, , 2021Thiebes et al, 2015;Reichenstein et al, 2019), in homeostatic plasticity (Rocchi et al, 2019), in stress related responses (Torres-Berrío et al, 2020;Schell et al, 2022;Yoshino et al, 2022), as well as in regulating contextual and spatial memory processes (Lu et al, 2021). Surprisingly, transcriptional profiling revealed that the upregulated genes upon miRNA-218 inhibition were more enriched in INs as compared to pyramidal neurons (Taylor et al, 2022).…”
Section: Mirna-218mentioning
confidence: 98%
“…Transient inhibition of miRNA-218 in the dorsal hippocampus in early postnatal life resulted in the disruption of early depolarizing GABAergic signaling, structural defects in dendritic spines in CA1, and increased intrinsic membrane excitability in CA3 pyramidal neurons resulting in a heightened hippocampal network activity and a predisposition to seizures. Previous work has shown that miRNA-218 is implicated in embryonic motor neuron development (Amin et al, 2015(Amin et al, , 2021Thiebes et al, 2015;Reichenstein et al, 2019), in homeostatic plasticity (Rocchi et al, 2019), in stress related responses (Torres-Berrío et al, 2020;Schell et al, 2022;Yoshino et al, 2022), as well as in regulating contextual and spatial memory processes (Lu et al, 2021). Surprisingly, transcriptional profiling revealed that the upregulated genes upon miRNA-218 inhibition were more enriched in INs as compared to pyramidal neurons (Taylor et al, 2022).…”
Section: Mirna-218mentioning
confidence: 99%